LAND ASSETS MANAGEMENT IN TERRITORIAL COMMUNITIES IN CONDITIONS OF RUSSIAN MILITARY AGRESSION IN UKRAINE: ORGANIZATIONAL AND FINANCIAL ASPECT - PATYTSKA, Khrystyna (Scientific journal «World of Finance», 2022)
Introduction. The approach to assets management in territorial communities has changed in conditions of Russian military aggression in Ukraine. Maintaining the state is the major task for all governance levels that requires the mobilization of economic entities to accumulate financial and human resources to oppose the enemy. The change of land assets management benchmarks on the national level has brought about a change of priorities in this area for territorial communities as their financial capacity directly depends on the opportunities to use the land as the main asset. It requires new approaches to asset management in communities. The purpose of the article is to define the features of land assets management in territorial communities in conditions of Russian military aggression in Ukraine. Methods. The research has been conducted using the methods of dialectical analysis, synthesis, and logical generalization, as well as comparison and formalization. Results. The article determines the following priorities of land assets management in territorial communities at the current stage: quick attraction of agricultural lands in the country to agricultural production in conditions of martial law; holding the sowing campaign and stimulation of agricultural goods production; efficient governmental support of agriculture. The change of land assets management terms at all levels and conducting production activities in agriculture directed at securing the resources accessibility, promotion of logistics chains, and financial assistance to economic entities are substantiated based on detecting the problems with sowing campaign in conditions of Russian military aggression in Ukraine and the analysis of governmental measures taken to overcome them. The change of proprieties in land assets management in territorial communities is explained.